Analysis of Work-Family Conflict on Working Woman Viewed From The Number of Children - Harini, Nathania Astria Rizki; Lopes De Carvalho, Lalita Sativanita; Supraba, Dellawaty; Rachmaningrum, Ratih Agustin (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Abstract: The existence of the times and gender equality are supporting factors in the depletion of the role of patriarchy in everyday life, this could be a trigger for the work-family conflict in women's lives today. The purpose of this study is to determine the effect of the number of children on work-family conflict in working women. This research is also evidence that there are still many problems around that can be studied more deeply to get a solution and also the novelty of science. The subjects in this study were working women who had children. This study uses quantitative methods and data collection using a questionnaire presented in the google form. To measure work-family conflict, a multidimensional scale was adapted by Septiani (2016) developed by Carlson, Kacmar, and Williams (2000). The measuring instrument consists of 18 statements which are divided into three aspects, namely time-based conflict, strain-based conflict, and behavioral conflict. All items are in the form of favorable statements. The data analysis technique used the chi-square test. The result of this study is that there is no significant effect between the number of children and the work-family conflict experienced by working women who have children. Keywords: Work-family Conflict; Career Woman; Children